Safety of Combination Vaccines with Whole Cell Pertussis Component - O. V. Perelygina; I. A. Alekseeva (Эпидемиология и вакцинопрофилактика)
We consider the safety of domestic products combined (DTP, Bubo Kok) containing whole-cell pertussis vaccine. DTP and Bubo Kok safety vaccines meet WHO requirements, EF and more rigid in some cases, the requirements of Russian regulatory documents. Thus, in assessing the safety of specific pertussis vaccine and complete neutralization of diphtheria and tetanus toxins, are administered to laboratory animals much larger doses of test products in comparison with the requirements of the WHO and the EP. In contrast to the WHO and the EP in the domestic requirements have stringent requirements for quantitative content in the non-adsorbed toxoids vaccine. Compared with foreign counterparts, domestic vaccines are significantly less anti-genetic load, that is responsible for their low reactivity, at the same time they possess the desired immunogenic activity.